Test Results Detection Specific Learning Difficulties for High School and Vocational High School Adolescents in Southeast Sulawesi - Haeba, Nurhaerani; Nursalam, Nursalam; Ampa, Andi Tendri (PPSDP International Journal of Education, 2025)
This study aimed to detect and describe the prevalence and types of Specific Learning Difficulties (SLDs) dyslexia, dysgraphia, and dyscalculia among Grade X students in senior high schools (SMA) and vocational high schools (SMK) in Southeast Sulawesi Province. A descriptive quantitative design was employed. The study population comprised all 50,483 Grade X students (37,113 from SMA and 13,370 from SMK). A sample of 5,675 students from 35 schools (11 SMA and 24 SMK) was assessed using the Specific Learning Difficulties Detection Test, which evaluated reading, writing, and arithmetic skills. This was supplemented by teacher questionnaires and student learning documentation. Data were analyzed descriptively to determine the number, proportion, and categories of SLDs. A total of 624 students were identified with SLDs: 417 from SMA and 207 from SMK. The prevalence was higher in SMA (12.9%) than in SMK (8.5%). Dyslexia was the most common type, followed by dyscalculia and then dysgraphia. The study also found that teacher understanding of SLDs was generally insufficient, hampering effective detection and intervention. The study recommends: Implementing systematic, periodic early detection programs for SLDs in schools. Providing targeted training for teachers to improve identification and intervention strategies for students with SLDs. Developing and adopting adaptive, inclusive teaching methods within SMA and SMK curricula to support diverse learning needs. These findings are intended as a foundation for regional governments and educational institutions to formulate policies that improve educational services tailored to individual student needs. This research provides the first comprehensive, data-driven snapshot of SLD prevalence among adolescents in Southeast Sulawesi, a region previously lacking such evidence. By highlighting the significant prevalence of SLDs particularly dyslexia at the secondary education level and linking it to a gap in teacher awareness, the study makes a critical contribution. It shifts the focus from a purely academic concern to a systemic one, offering concrete, evidence-based recommendations for early detection, teacher training, and inclusive policy-making to address this educational challenge.